Peranan pengalaman mengajar dalam hubungan antara komitmen terhadap profesion dengan prestasi kerja - Shaari, Abdull Sukor; Yaakub, Noran Fauziah; Awang Hashim, Rosna (Universiti Utara Malaysia, 2004)
The study aimed to (1) identify the level of commitment to the profession among secondary school teachers, (2) to identify its relationship with job performance,and (3) to identify the influence of teaching experience as a moderator of the relationship between commitment to the profession and job performance. Data were collected through survey using a questionnaire. This study employed stratified random sampling involving a total of 370 teachers from 108 secondary schools in Kedah. The findings revealed that most of the respondents showed high commitment to their profession. There is a significant and positive relationship between commitment and job performance. Teaching experience was a significant moderator of the relationship between commitment to the profession and job performance.